2020
DOI: 10.2478/ers-2020-0030
|View full text |Cite
|
Sign up to set email alerts
|

Macroeconomic Conditions of the Financial Efficiency of Food Industry Enterprises

Abstract: SummarySubject and purpose of work: The subject of this research was the financial efficiency of large food industry enterprises in Poland, and its aim was to determine the strength and direction of the impact of key macroeconomic factors on the level of financial efficiency of those enterprises.Materials and methods: Data from the Central Statistical Office, the results of own research as well as literature on the problem were used. The research period covered the years 2005-2018. Dynamic panel models were ap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 8 publications
(6 reference statements)
0
2
0
Order By: Relevance
“…Macroeconomic risks encompass a broad range of factors including economic, social, political, technological, and environmental influences that indirectly affect the insurance industry. Typically, these risks are beyond the direct control of any single insurance company and can impact the industry in profound and unpredictable ways (Juszczyk et al, 2020;Neilbergs, 1998):…”
Section: Macroeconomic Risksmentioning
confidence: 99%
“…Macroeconomic risks encompass a broad range of factors including economic, social, political, technological, and environmental influences that indirectly affect the insurance industry. Typically, these risks are beyond the direct control of any single insurance company and can impact the industry in profound and unpredictable ways (Juszczyk et al, 2020;Neilbergs, 1998):…”
Section: Macroeconomic Risksmentioning
confidence: 99%
“…The economic crisis of 2008/2009 exacerbated the already significant decline in the Hungarian agriculture and food sector, which in turn reduced its former dominant role among the V4 countries (Baráth, Nagy, Szabó, 2010 in Fenyves). Juszczyk et al (2020), examining large Polish food companies between 2005 and 2018, found that an increase in the inflation rate had a negative effect on the financial efficiency of firms, while increases in GDP, consumption and accumulation had a positive effect.…”
Section: General Trends and History Of The Hungarian Food Industrymentioning
confidence: 99%
“…According to the assumptions of neoclassical economics, all market participants are assumed to have the same access to information (Juszczyk et al 2020). However, economic reality differs from this model, because in many cases this assumption is wrong (Stiglitz et al 2002).…”
Section: Introductionmentioning
confidence: 99%